Enhanced engraftment of human myelofibrosis stem and progenitor cells in MISTRG mice - Lysenko, V; Wildner-Verhey van Wijk, N; Zimmermann, K; Weller, M-C; Bühler, M; Wildschut, MHE; Schürch, P; Fritz, C; Wagner, U; Calabresi, L; Psaila, B; Flavell, RA; et al. (American Society of Hematology, 2020)
The engraftment potential of myeloproliferative neoplasms in immunodeficient mice is low. We hypothesized that the physiological expression of human cytokines (macrophage colony-stimulating factor, interleukin-3, granulocyte-macrophage colony-stimulating factor, and thrombopoietin) combined with human signal regulatory protein α expression in Rag2−/−Il2rγ−/− (MISTRG) mice might provide a supportive microenvironment for the development and maintenance of hematopoietic stem and progenitor cells (HSPC) from patients with primary, post–polycythemia or post–essential thrombocythemia myelofibrosis (MF). We show that MISTRG mice, in contrast to standard immunodeficient NOD.Cg-PrkdcscidIl2rgtm1Wjl/SzJ and Rag2−/−Il2rγ−/− mice, supported engraftment of all patient samples investigated independent of MF disease stage or risk category. Moreover, MISTRG mice exhibited significantly higher human MF engraftment levels in the bone marrow, peripheral blood, and spleen and supported secondary repopulation. Bone marrow fibrosis development was limited to 3 of 14 patient samples investigated in MISTRG mice. Disease-driving mutations were identified in all xenografts, and targeted sequencing revealed maintenance of the primary patient sample clonal composition in 7 of 8 cases. Treatment of engrafted mice with the current standard-of-care Janus kinase inhibitor ruxolitinib led to a reduction in human chimerism. In conclusion, the established MF patient-derived xenograft model supports robust engraftment of MF HSPCs and maintains the genetic complexity observed in patients. The model is suited for further testing of novel therapeutic agents to expedite their transition into clinical trials.